Paratrygon aiereba irradiated anti-mucus serum reduce edematogenic activity induced in experimental model. (30th April 2020) - Coelho Thomazi, Gabriela Ortega; da Costa, Andrea; Rodrigues, Jaqueline Polizeli; Alves, Glaucie Jussilane; Prezotto Neto, José Pedro; de Oliveira Turíbio, Thompson; Rocha, André Moreira; da Silva Aires, Raquel; Seibert, Carla Simone; Spencer, Patrick Jack; Galisteo Júnior, Andrés Jimenez; de Andrade Júnior, Heitor Franco; et al.
Abstract: Accidents by freshwater stingrays are common in northern Brazil, there is no specific therapy for high morbidity and local tissue destruction. The irradiation of venoms and toxins by ionizing radiation has been used to produce appropriate immunogens for the production of antisera. We planned to study the efficacy of stinging mucus irradiation in the production of antisera, with serum neutralization assays of edematogenic activity and quantification of cytokines performed in animal models of immunization with native and irradiated mucus of Paratrygon aiereba, a large freshwater stingray. Antiserum potency and its cross-reactivity with mucus from other freshwater stingrays were detected by ELISA. Immunization models demonstrated the ability to stimulate a strong humoral response with elevated levels of serum IgG detectable by ELISA, and both native and irradiated mucus were immunogenic and capable of recognizing mucus proteins from other freshwater neotropical stingrays. Mucus P. aiereba causes cellular and humoral adaptive immune responses in cells of immunized mice producing antibodies and cytokines such as TNF-α, IL-6 and IL-17. Rabbit antisera immunized with mucus from P. aiereba irradiated at 2 kGy showed a significant reduction of mucus-induced edematogenic activity in mice. Our data suggest that the use of antisera against freshwater stingray mucus show the possibility of specific therapy for these accidents. Highlights: Native and irradiated mucus from Paratrygon aiereba were immunogenic. Mucus stimulate a strong humoral response with elevated levels of IgG. Antiserum is capable of recognizing mucus proteins from other freshwater stingrays. Rabbit antisera immunized with mucus irradiated reduced of edematogenic activity. Native and irradiated mucus induces the production of cytokines.